Respuesta :

Answer:

x = 0

y = 2

Step-by-step explanation:

3x + 9y = 18 ---------eqn 1

y = x + 2---------eqn 2

Substitute eqn 2 into eqn 1, for the value of y

3x + 9( x + 2) = 18

3x + 9x + 18 = 18

12x + 18 = 18

12x = 18 -18

12x = 0

Divide both sides by 12 , to get the value of x.

12x/ 12 = 0/12

x = 0

Substitute x = 0 into eqn 2

y = x + 2

y = 0 +2

y = 2

Hint: to confirm the values

x = 0

y = 2

Let's take eqn 1 ,

3x + 9y = 18

3(0) + 9(2)

= 0 + 18

= 18

Correct

Let's take eqn 2

y = x + 2

Let's find y

y = 0 + 2

y = 2

Correct too